2020
DOI: 10.1038/s41598-020-66838-5
|View full text |Cite
|
Sign up to set email alerts
|

Visual sense of number vs. sense of magnitude in humans and machines

Abstract: Numerosity perception is thought to be foundational to mathematical learning, but its computational bases are strongly debated. Some investigators argue that humans are endowed with a specialized system supporting numerical representations; others argue that visual numerosity is estimated using continuous magnitudes, such as density or area, which usually co-vary with number. Here we reconcile these contrasting perspectives by testing deep neural networks on the same numerosity comparison task that was adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 73 publications
5
44
0
Order By: Relevance
“…Previously, it was suggested that the reported number sense might be observed because of the correlation between the numerosity and other continuous magnitudes such as total area, because it is hardly possible to design visual stimuli in which numerosity is completely independent of other nonnumerical visual magnitudes (e.g., if the total area is fixed, then the single dot size must decrease as numerosity increases) (35). However, this scenario was refuted in a number of commentaries (36)(37)(38)(39)(40) and after further studies (41,42), from the fact that the observed number sense does not depend on various visual features in each controlled test. To address this issue carefully, we devised a new numerosity comparison task that could be successfully performed, only when the network makes decisions based on estimation of abstract numerosity.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was suggested that the reported number sense might be observed because of the correlation between the numerosity and other continuous magnitudes such as total area, because it is hardly possible to design visual stimuli in which numerosity is completely independent of other nonnumerical visual magnitudes (e.g., if the total area is fixed, then the single dot size must decrease as numerosity increases) (35). However, this scenario was refuted in a number of commentaries (36)(37)(38)(39)(40) and after further studies (41,42), from the fact that the observed number sense does not depend on various visual features in each controlled test. To address this issue carefully, we devised a new numerosity comparison task that could be successfully performed, only when the network makes decisions based on estimation of abstract numerosity.…”
Section: Discussionmentioning
confidence: 99%
“…All models for numerical cognition come roughly to the same results, namely, the ability of artificial neural networks to simulate human and non-human animals' behaviors in numerical judgments, i.e., the discrimination of one numerosity from another (Rapp et al, 2020), comparison tasks for relationships of sameness (Nasr et al, 2019), or inequality (Testolin et al, 2020a). However, their relevant implications and proposals regarding the implementation of numerical ability rely on their architectures and main functional properties.…”
Section: Neural Networkmentioning
confidence: 90%
“…These types of neural networks have been also usefully employed in order to disentangle the spiny issue of nonnumerical perceptual features that covary with numerosity (Testolin et al, 2020a). Using the stimulus space designed in another study (DeWind et al, 2015), they have been able to statistically estimate the contribute of each non-numerical feature to numerical comparison tasks.…”
Section: Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, if guppies succeeded only with the easier ratio (0.6), we would conclude that the conditioning chamber allows to study learning but does not provide increased learning efficiency in the context of numerical discrimination. Besides manipulating numerosity, we also manipulated other visual features to investigate the impact of non-numerical magnitudes in discrimination performance (see 25 ). In the "incongruent" condition, cumulative area was equated in the two stimuli, implying that individual item size was incongruent with number (i.e., stimuli with larger numbers had smaller items).…”
Section: Automatic Conditioning Chambermentioning
confidence: 99%